The The Influence of Product Attributes, Brand Image, and Lifestyle on Xiaomi Smartphone Purchase Decision (Quantitative Study on Balitar Islamic University Students) - Novita Putri Diantanti; Aqidatul Izah (Universitas Islam Balitar, 2021)
Product attribute and brand image are a unity that builds the strength of a product. One of the considerations of consumers in choosing a product is the quality offered. In addition, consumer lifestyles are also a factor in purchase decision. This study aims to determine the influence of product attributes, brand image, and lifestyle on Xiaomi smartphone purchase decisions on Universitas Islam Balitar students. The research method used was a survey with a quantitative research approach. The sampling technique used was purposive sampling. Data collection was carried out by distributing questionnaires to Universitas Islam Balitar students who use Xiaomi smartphones. The data analysis technique used is the t test (partial) and multiple linear regression analysis to 100 respondents. Based on the results of partial tests conducted, it is known that the product and lifestyle attributes partially have a significant influence on the purchase decision variable, while the brand image variable does not significantly influence the purchase decision variable. The better product attributes and product innovations offered, Xiaomi will be able to embrace all walks of life with different lifestyles so that will affect the level of consumer purchase decision.